ANALISIS TINGKAT KETERAMPILAN DASAR TENIS MEJA PADA SISWA KELAS XI PUTRA SMA NEGERI 1 WATUBANGGA - Nur Indah; Muhammad Rusli; Suhartiwi (Universitas Halu Oleo, 2021)
This research was based on the discovery of the potential of athletes, especially in the game of table tennis at SMA Negeri 1 Watubangga. In order for the potential of these athletes to be maximally developed, it is necessary to classify the basic skills level of table tennis in class XI male students of SMA Negeri 1 Watubangga. This study aims to determine the level of basic table tennis skills in class XI male students of SMA Negeri 1 Watubangga. The research method used is descriptive analysis research, the research instrument in the form of a table tennis basic skills test consisting of six test items, namely bouncing the ball with a racket, forehand, backhand, service, smash, and defense. The study population was the male students in class XI SMA Negeri 1 Watubangga, totaling 74 male and the sample in this study was taken by purposive sampling technique, namely by considering the gender of men so that the sample in this study. are all male students of class XI SMA Negeri 1 Watubangga totaling 74 people and the data analysis technique in this study uses a percentage formula. Based on the results of the study, data on the basic skills level of table tennis in class XI male students SMA Negeri 1 Watubangga, excellent category at 0%, good category by 13%, medium category by 49%, in the poor category 26% and inadequate category 12% .